2004
DOI: 10.1366/000370204773580220
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification of Carotenoids and Fat in Atlantic Salmon (Salmo Salar L.) by Raman Spectroscopy and Chemometrics

Abstract: Raman spectroscopy (785 nm excitation) was used to determine the overall carotenoid (astaxanthin and cantaxanthin) and fat content in 49 samples of ground muscle tissue from farmed Atlantic salmon (Salmo salar L.). Chemically determined contents ranged from 1.0 to 6.8 mg/kg carotenoids and 36 to 205 g/kg fat. In addition to the raw Raman spectra, three types of spectral preprocessing were evaluated: the first derivative, subtraction of the fitted fourth-order polynomial (POLY), and the intensity normalized ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 24 publications
3
26
0
1
Order By: Relevance
“…Raman spectroscopy has been shown to be a useful tool to study structural changes in solid food systems such as fish and meat (Brøndum, Byrne, Bak, Bertelsen, & Engelsen, 2000;Herrero, 2008a;Herrero, Cambero, Ordóñez, de la Hoz, & Carmona, 2008;Pedersen, Morel, Andersen, & Engelsen, 2003) and to determine structural changes that occur during processing and storage of fish and seafood products such as surimi (Bouraoui, Nakai, & Li-Chan, 1997;Herrero, Carmona, & Careche, 2004;Herrero, Carmona, García, Solas, & Careche, 2005;MoosaviNasah, All, Ismail, & Ngadi, 2005). In addition, some authors have studied carotenoids and fat by Raman spectroscopy in salmon muscle (Afseth, Wold, & Segtnan, 2006;Henmi, Hata, & Takeuchi, 1990;Wold, Marquardt, Dable, Robb, & Hatlen, 2004). Characterization and discrimination of irradiated starch using Raman spectroscopy has been also performed (Kizil & Irudayaraj, 2006;Kizil, Irudayaraj, & Seetharaman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy has been shown to be a useful tool to study structural changes in solid food systems such as fish and meat (Brøndum, Byrne, Bak, Bertelsen, & Engelsen, 2000;Herrero, 2008a;Herrero, Cambero, Ordóñez, de la Hoz, & Carmona, 2008;Pedersen, Morel, Andersen, & Engelsen, 2003) and to determine structural changes that occur during processing and storage of fish and seafood products such as surimi (Bouraoui, Nakai, & Li-Chan, 1997;Herrero, Carmona, & Careche, 2004;Herrero, Carmona, García, Solas, & Careche, 2005;MoosaviNasah, All, Ismail, & Ngadi, 2005). In addition, some authors have studied carotenoids and fat by Raman spectroscopy in salmon muscle (Afseth, Wold, & Segtnan, 2006;Henmi, Hata, & Takeuchi, 1990;Wold, Marquardt, Dable, Robb, & Hatlen, 2004). Characterization and discrimination of irradiated starch using Raman spectroscopy has been also performed (Kizil & Irudayaraj, 2006;Kizil, Irudayaraj, & Seetharaman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Further, VIS showed to be efficient in estimation of pigments in the fillet. Wold et al [8] showed that Raman spectroscopy was a suitable method for none destructive estimation of pigments (r = 0.95) and fat % (r = 0.97) in the ground salmon meat.…”
Section: Methods To Measure Quality Traitsmentioning
confidence: 99%
“…Studies involving marine organisms are emerging, and Raman analysis has been applied to animals, algae, and dinoflagellates, which have identified carotenoids, sterols, nonsubstituted conjugated polyenals, chromophores of green fluorescent proteins (GFPs), chlorophylls, melanins, and mycosporine-like amino acids (MAAs). Carotenoids have been identified from corals [140][141][142], mollusks [143,144], lobster carapace [145,146], fish [147], brown algae [148] and dinoflagellates [149]. Polyenals are a recently described class of polyenes identified from shells of mollusks [143,144] and octocorals [140][141][142][150][151][152][153].…”
Section: Application Of Raman Scattering To Marine Natural Products: mentioning
confidence: 99%